Quality evaluation of Idli prepared from betel leaves essential oil nanoemulsion treated stored batter - Sangeetha Karunanithi; Proshanta Guha; Prem Prakash Srivastav (Food Chemistry Advances)
The demand for clean-label, natural preservation in fermented foods requires innovative methods to extend shelf-life while maintaining quality. This study evaluates Idli quality from batter stored with and without 5% betel leaf essential oil-based nanoemulsion (BLEONE) at 30 °C and 4 °C. Color, texture, microbial growth, proximate composition and sensory attributes were assessed using standard methods, with statistical analysis via ANOVA and Tukey's post-hoc test (p < 0.05). BLEONE-treated Idli showed 30.2% reduced hardness, 17.1% better color retention, and 0.61 log CFU/g less microbial growth after 5 days, inhibiting harmful microbes and supporting beneficial lactic acid bacteria. At 30 °C, BLEONE-treated Idli maintained quality for 7 days versus 2 days for controls. Moisture, protein, and fat retention improved by 3.4%, 7.3%, and 6.2%. Sensory scores for taste, mouthfeel, and acceptability increased by 3.5%, 4.1%, and 3.8% after 10 days at 4 °C. BLEONE-treated batter produced acceptable Idli for up to 25 days at 4 °C, compared to 10 days for controls, extending shelf-life by 150%. This study shows BLEONE is an effective natural preservative for Idli, extending shelf-life and maintaining quality at ambient and refrigerated temperatures. These findings suggest potential for clean-label preservation methods for fermented foods, potentially revolutionizing the food preservation industry.